Works Created Within the Employment Relationship - Maneva, Veselina (Yearbook of the Law Department, 2019)
The research and analysis of the creative achievements created in the context of employment, have always asked a number of questions related to the nature of these works, with the rights that arise for the employer and author, with the manner of their enforcement and payment of fair remuneration. The institute of the official work is established both in the system of copyright and in industrial legislation. It is a means of regulating the relationship between employer and creator. Theory and practice increasingly determine the need for deeper and more comprehensive regulation of these relations and overcoming the existing gaps.